Delivering HIV and TB services amidst the COVID-19 pandemic in Indonesia: a qualitative study of challenges and mitigation strategies - Luh Putu Lila Wulandari; Srila Nirmithya Salita Negara; Siska Dian Wahyuningtias; Yusuf Ari Mashuri; I Wayan Cahyadi Surya Distira Putra; Nasser Fardousi; Riris Andono Ahmad; David Boettiger; Ari Probandari; Yanri Wijayanti Subronto; Virginia Wiseman; Marco Liverani (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background Indonesia has the second-highest burden of tuberculosis (TB) globally and is experiencing one of the fastest-growing HIV epidemics worldwide. The COVID-19 pandemic disrupted access to essential health services, including those for TB and HIV, due to health system overload, social distancing measures, and negative economic repercussions on the health sector and the population. An in-depth understanding of these challenges and the health system responses to mitigate the negative impact of the pandemic on TB and HIV services is crucial to building health system resilience and preparing for future emergencies. # Methods This qualitative study, conducted in two cities in Indonesia, explored the impact of the COVID-19 pandemic on TB and HIV services including mitigation strategies to sustain the provision of testing and treatment in the midst of the pandemic. Between February and June 2022, semi-structured interviews were conducted with 16 healthcare workers and 16 clients at nine health centers (puskesmas), three hospitals, and one Community Center for Lung Health in Bandung and Yogyakarta. Themes were identified from transcripts using open and selective coding and then refined. # Results Extraordinary measures were implemented in health facilities to sustain TB and HIV service delivery, and prevent the spread of COVID-19, including testing of clients for COVID-19 before receiving medical care, physical distancing when visiting healthcare facilities, revised schedules for medicine dispensing, involvement of community health workers and peers in community outreach activities such as the home delivery of medicines, and the use of telemedicine. Challenges encountered during the implementation of these strategies included medicine stock-outs, health worker overload, lack of sufficient client-provider interaction and technical difficulties when implementing telemedicine, and the risk or fear of exposure to COVID-19 among the community health workers and peers. # Conclusions Significant efforts were made to mitigate disruptions to TB and HIV services during the COVID-19 pandemic. However, some challenges were encountered. Key policy recommendations to strengthen pandemic preparedness include investing in local manufacturing and robust drug supply networks to prevent medicine shortages, and supporting community health workers to alleviate workload issues, reduce the risk of disease exposure, and explore the potential for a financial incentive system. Equally vital is the need to invest in staff training and education, as well as implementing user-friendly telemedicine technologies.